MODEL PEMBELAJARAN KASTERI PRESTO DALAM MENINGKATKAN HASIL BELAJAR PAI DAN BUDI PEKERTI - Rochmatin, Siti (QUALITY, 2019)
This study aims to increase the enthusiasm and learning outcomes of the Prophet'sHijrah to Medina with the learning model of Presto Class VII F Middle School 6Salatiga in the even semester of 2016-2017. This research was conducted in 6months, from January to July 2017, both from the preparation of proposals,compilation of instruments, collecting data, implementing Class Actions,processing and analyzing values, to preparing reports. The place of research inSMP Negeri 6 Salatiga. The research subjects were students of class VII F SMPNegeri 6 Salatiga in the even semester 2016-2017 which numbered 15 people. Datacollection techniques initially took value in the last semester about the results oflearning Islamic history, then carried out 2 cycles, each cycle consisting of fourstages, namely planning, implementation, observation and reflection, ending witha written test, then assessing and reflecting to find out the success of the researchobjectives is according to what has been formulated. Seeing the values in the initialconditions which experienced an average of only 42.66, while after the actioncarried out in the first cycle increased to 53.60. this experienced a very significantincrease, namely 24.64%, while in the second cycle reached an average value of78, compared to the value in the first cycle increased by 45.52% as well.Keywords: learning outcomes, migration of the Prophet, Kasteri Presto.